Craneocervical posture in children after treatment with chincap: a pilot study - Pérez-O., Luis Javier; Gómez-D. , Sandra; Llano-S. , Elizabeth; Rivera-P., Wbeimar Andrey (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: the aim of this study was to describe the changes in the craniocervical posture in children with skeletal class iii malocclusion (prognathic mandible) after wearing chincap with lower occlusal bite plane. Methods: the sample consisted of eleven children (7 girls and 4 boys). three lateral cephalic radiographs were taken for each child with the head in natural position (“mirror position”), with light occlusal contact. The first radiograph (T1) was taken before wearing the chincap, the second (t2) was taken four months after wearing the appliance and the third (t3) was taken four months after removing the chincap. Specific angular and linear dimensions were used, the comparison within the group was performed using Descriptive analysis and the normality (shapiro-Wilk) y Friedman signed rank test. Results: statistical analysis didn’t show significant changes in any of the angular and linear measurements analyzed nor at any of the times studied. Conclusion: even though there is a great individual variability in the cranial, cervical and craniocervical posture of the tested children, in general, there were no statistical significant changes in cervical posture after treatment with chincap and lower occlusal bite plane.